1993
DOI: 10.2307/1131545
|View full text |Cite
|
Sign up to set email alerts
|

Linking Employment to Attachment: The Mediating Effects of Maternal Separation Anxiety and Interactive Behavior

Abstract: This study examined the effects of maternal employment and separation anxiety on maternal interactive behavior and infant attachment. 73 mother-infant pairs participated in a laboratory free-play session when infants were 5 and 10 months of age and in the Strange Situation when the infants were 18 months of age. Maternal feelings about being separated from her infant were assessed by questionnaire at 5 months. Employed mothers returned to work before the infants' fifth month, and nonemployed mothers did not wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
1
2

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 24 publications
3
40
1
2
Order By: Relevance
“…In two such studies, high scores on a separation anxiety questionnaire were associated with overprotective maternal behavior (Hock, McBride, & Gnezda, 1989;Stifter, Coulehan, & Fish, 1993); in one, mothers' retrospective accounts of felt anxiety after a premature birth were related to intrusive maternal behavior at 6 months' postpartum (Wijnorks, 1999); and in several studies, prenatal anxiety was related to intrusive and controlling behavior during the early postpartum period (Field, Sandberg, Vega-Lahr, Goldstein, & Guy, 1985;Heinicke, Diskin, Ramsey-Klee, & Given, 1983). Added to this list is the study of Feldman, Greenbaum, Mayes, and Erlich (1997), which showed that an increase in mothers' trait anxiety scores from 3 to 9 months' postpartum was associated with a concurrent decrease in maternal sensitivity (but not intrusiveness) (also see Mertesacker, Bade, Haverkock, & Pauli-Pott, 2004).…”
Section: Anxious-overactive Mothersmentioning
confidence: 99%
“…In two such studies, high scores on a separation anxiety questionnaire were associated with overprotective maternal behavior (Hock, McBride, & Gnezda, 1989;Stifter, Coulehan, & Fish, 1993); in one, mothers' retrospective accounts of felt anxiety after a premature birth were related to intrusive maternal behavior at 6 months' postpartum (Wijnorks, 1999); and in several studies, prenatal anxiety was related to intrusive and controlling behavior during the early postpartum period (Field, Sandberg, Vega-Lahr, Goldstein, & Guy, 1985;Heinicke, Diskin, Ramsey-Klee, & Given, 1983). Added to this list is the study of Feldman, Greenbaum, Mayes, and Erlich (1997), which showed that an increase in mothers' trait anxiety scores from 3 to 9 months' postpartum was associated with a concurrent decrease in maternal sensitivity (but not intrusiveness) (also see Mertesacker, Bade, Haverkock, & Pauli-Pott, 2004).…”
Section: Anxious-overactive Mothersmentioning
confidence: 99%
“…Tüm bu spekülasyon-ların kanıta dayandırılması için emzirmenin süre, yön-tem ve etkileşim parametrelerini içeren doğrudan gözlem bulguları ile anne sütü içeriğinin ilişkisini araş-tıran çalışmalara gereksinim vardır. Anne ve bebeğin erken dönemdeki etkileşimi tarafından belirlenen, insan yaşamındaki ilk temel ilişki olan ve doğumdan sonraki ilk saatlerde ve gün-lerde başlayan bağlanma ilişkisinin özellikleri annenin kendi bebekliğinde annesiyle geliştirdiği bağlan-ma özelliklerinden de etkilenebilmektedir (16,(21)(22)(23)(24) . Bu bağlamda kendi annesiyle güvenli olmayan bağlan-ma geliştirmiş bir annenin, kendi bebeğiyle güvenli bağlanma geliştirmesinde sorun olabileceği ve bebek doğduktan sonraki ilk etkileşim olan emzirmenin anneye ait bu risk etmeninden etkilenebileceği düşü-nülebilir.…”
Section: Discussionunclassified
“…Bağlanma ilişkisinin; bebeklerin doğuştan gelen emme, izleme, gülümseme, ağlama, dokunma gibi davranışları aracığıyla anne ile ilk etkileşimi başlata-rak doğumdan sonraki ilk saatlerde ve günlerde baş-ladığı belirtilmektedir (16) . Anne-bebek etkileşiminde çok önemli bir yere sahip olan emzirmenin anne ile bebek arasında bir bağ oluşturarak güvenli bağlan-manın gelişmesinde önemli bir işlev gördüğü düşü-nülmektedir (17) .…”
Section: Anneye Ait Psikososyal Risk Etmenlerinin Anne Sütü Elektroliunclassified
“…Perhaps as a consequence of this guilt, mothers who reported feelings of high anxiety and whose infants used part-time child care were more physically and verbally affectionate with them on arrival at care than mothers who were highly anxious and had infants in full-time care (Storm & Ridley-Johnson, 1995). Research has similarly indicated that employed mothers who reported high levels of separation anxiety were more likely to overstimulate their infant than less anxious mothers and that these infants did not have much influence over the pace or the focus of their interactions during the separation process (Stifter, Coulehan, & Fish, 1993). Other factors which have been found to affect parent separation behaviours include early and prolonged mother-infant separation (Leifer & Others, 1972), levels of maternal responsiveness (Lollis, 1990;Stayton & Ainsworth, 1973) and the quality of parent-infant relations (Anderson, 1980).…”
Section: Parental Behaviours During Separationmentioning
confidence: 99%
“…Categories were also used to identify and count the frequencies of infant behaviours and activities following their parent's departure (see Appendix 2). Both sets of categories were based upon previous child care-based research findings on parent-child attachment and separation anxiety (Fein, Gariboldi, & Boni, 1993;Fein, 1995;Owen, Ware, & Barfoot, 2002;Pederson et al 1998;Rolfe, 1988;Stifter, Coulehan, & Fish, 1993;Storm & Ridley-Johnson, 1995;Wille, 1998). The category codes and items of behaviour in the Inventory were included if they reflected this study's Australian child care context.…”
Section: Observational Toolsmentioning
confidence: 99%